: № 56 (1788) (1982)
Титульного листа нет, описание составлено по обложке Для служебного пользования, экз. № 92 Экземпляры: УКП (20240505) / Инвентарный номер: АП19820069 / Сис.шифр: 65.31 / Авт.знак: И 93 / ГРНТИ: 06.35.33 / ББК: 65.31-05